-1
-3 - 4 = -7 (minus seven)
676
-4 + -3 = -7
(-3)-(4)=(-3)+4=1 Minus times minus equals plus. The reason for this we need not discuss.
No.
when you're doing a problem like that use this trick. let's say you have 3 to the -7 power minus 3 to the 4 power. -7 - 4 can also be shown as -7 + -4. i switched the minus sign to a plus sign and because i did that, i had to switch the positive 4 to a negative 4. so i got 3 to the -7 power plus 3 to the -4 power.
6 - 34 = -75
7
12 - 4 = (1 * 1) - 4 = 1 - 4 = -3
0.0000115 = 1.15 X 10 -5 ---------------------is this what you mean? Not - 4 but - 5 .
243 - 32 = 211
-4 basically you take 5 from one!
4²-3+11-12 = 16-3+11-12 = 12
Since the base is the same, you can subtract the exponents in this case, so it is 4 to the power (9 minus 3).
If you mean 3 and 1/4 minus 2 and 1/3 then it is 11/12
4(10x4 + 3)(10x4 - 3)